Application of different edge detection methods for faults identification in Anza Basin, Kenya - Gege Li; Qing Chen; Bingqiang Yuan; Xianfeng Tan; Hao Chen; Xiaoyu Huang; Lang Pan (Terrestrial, Atmospheric and Oceanic Sciences)
Abstract The shape of gravity anomalies changes due to the disruption of geological bodies’ continuity by fault structures, and their planar contour line characteristics are an important basis for dividing fault structures. However, the traditional potential field boundary identification method has limited ability to detect the boundaries of buried deep geological bodies. Therefore, geophysicists at home and abroad have proposed various new techniques for potential field boundary identification. These techniques aim to effectively and rapidly extract or enhance weak anomaly information about geological bodies’ boundaries. They also aim to delineate the distribution range of field sources. This paper systematically analyzes the principles of various gravity potential field boundary identification methods. It also uses various methods to process and interpret the Bouguer gravity anomalies in the Anza Basin of Kenya. Additionally, it determines the fault system in the basin and carries out structural zoning. The results of the processing of various gravity boundary identification methods with the gravity data in the study area show that a gravity gradient zone is developed in the Anza Basin, where the Bouguer gravity anomalies are all negative and exhibit a large variation range, overall showing a high-southwest and low-northeast trend. The analysis of residual gravity anomaly yields results indicating that the local structure of the study area has obvious structural pattern of the “east-west zone and north-south block”. The study area exhibits developed faults, which can be mainly categorized into two sets with northwest direction and northeast direction orientations. Small-scale northeast-direction faults cut off larger-scale northwest-direction faults. Six tectonic zones were recognized in combination with the gravity anomalies and seismic data in the study area, which include eastern depression, southern uplift, central bulge, western depression, northern slope and western uplift.